EU Go Green: Is It Impacted by Carbon, Crude Oil, and Non-Renewable Stock Index? - Alexander Daniel Tan; Jessica Angelitta Vania; Steven Wijaya; Shinta Amalina Hazrati Havidz (Unversitas Muhammadiyah Mataram, 2024)
Abstract: This research investigated the impact of carbon pricing, crude oil prices, and non-renewable stock indices on the price dynamics of renewable energy stock indices within the European Union. The objective was to analyze how these factors influence price fluctuations and further enhance investment growth in the renewable energy sector. The Rebalancing Aggregate Real Carbon Price (GRCP) was proposed as a novel independent variable representing carbon price indicators alongside the European Union Allowance (EUA). This research used daily time series data, thus applying Ordinary Least Squares (OLS) with robust standard error as the methodology. OLS with robust standard error is a standard method to ensure the reliability of regression analysis. The results showed that crude oil prices and the EUA exhibit an insignificant negative effect on renewable energy stock returns. Meanwhile, the non-renewable energy stock index showed a positive and significant impact on renewable energy stock returns (p<0.01), indicating that better performance in the non-renewable energy sector increases the influence of environmental issues. GRCP also positively impacted renewable energy stocks, p<0.01 for OMX and p<0.05 for ERIX. This study showed that renewable energy investments can be a solid alternative to non-renewable stocks for investors. For policymakers, strengthening carbon pricing policies across sectors and regions was critical to supporting the transition to renewable energy, as GRCP plays an essential role in shaping stock price dynamics. Thus, in the future, the effectiveness of carbon pricing policies needs to be analyzed to improve global environmental strategies.